2018
DOI: 10.1002/jcph.1282
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and Pharmacodynamic Evaluation of Intravenous Levetiracetam in Children With Epilepsy

Abstract: This study aimed to evaluate the safety and tolerability of intravenous (IV) levetiracetam (LEV) as a monotherapy in children aged 1 month-16 years and to explore the pharmacokinetics (PK) of IV LEV and the time to seizure after IV then oral administration of LEV in pediatric children with epilepsy. Children diagnosed with acute unprovoked seizures requiring in-hospital IV LEV administration were included. After administration, the clinical seizure outcomes, side effects, and the Korean-Child Behavior Checklis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 43 publications
(48 reference statements)
1
20
0
Order By: Relevance
“…Reports have suggested that miR‐135a‐5p confer neuronal protection in mice with Alzheimer's disease by regulating potassium channels. KCNQ3 is a gene encoding a potassium ion channel and is widely expressed in brain and sympathetic ganglia . Potassium channels are closely related to the electrical activity of central neurons, and their structural and functional abnormalities will alter neuronal excitability and cause seizures .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports have suggested that miR‐135a‐5p confer neuronal protection in mice with Alzheimer's disease by regulating potassium channels. KCNQ3 is a gene encoding a potassium ion channel and is widely expressed in brain and sympathetic ganglia . Potassium channels are closely related to the electrical activity of central neurons, and their structural and functional abnormalities will alter neuronal excitability and cause seizures .…”
Section: Discussionmentioning
confidence: 99%
“…KCNQ3 is a gene encoding a potassium ion channel and is widely expressed in brain and sympathetic ganglia. 33 Potassium channels are closely related to the electrical activity of central neurons, and their structural and functional abnormalities will alter neuronal excitability and cause seizures. 34 During the current experiment, the online prediction software Targetscan was used to demonstrate that miR-135a-5p could bind to the 3 0 UTR of KCNQ3.…”
Section: Discussionmentioning
confidence: 99%
“…Sneck et al [13] enrolled only healthy subjects, Pigeolet et al included both patients and healthy subjects [14], and the other studies were conducted in patients with epilepsy [15-26]. Eight of the fourteen studies enrolled paediatric patients [15, 17, 18, 20, 21, 24-26]; 2 studies were conducted in neonates [18, 21], 4 studies in children less than 18 years of age [15, 20, 25, 26], and 2 studies included both children and adults [17, 24]. Three study only enrolled adults [13, 14, 19], and the other three studies included elderly patients of over 70 years [16, 22, 23].…”
Section: Resultsmentioning
confidence: 99%
“…The LEV PK for oral formulations was described with a one-compartment model with first-order absorption and elimination, and for injections was described with a one- or two- compartment model with first order elimination. Two studies conducted in neonates [18, 21], three in children [20, 26], and five in adults were based on sparse sampling data from the routine clinical TDM settings [16, 17, 19, 22, 23], and other four studies included intensive sampling data [13-15, 25]. The number of participants in each study ranged from 7 to 524, with LEV observations per individual ranging from 1 to 10.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation